Safety of azithromycin in infants under six months of age in Niger: A community randomized trial. - Catherine E Oldenburg; Ahmed M Arzika; Ramatou Maliki; Mohamed Salissou Kane; Elodie Lebas; Kathryn J Ray; Catherine Cook; Sun Y Cotter; Zhaoxia Zhou; Sheila K West; Robin Bailey; Travis C Porco; et al. (Public Library of Science (PLoS), 2018)
BACKGROUND:Mass azithromycin distribution reduces under-5 child mortality. Trachoma control programs currently treat infants aged 6 months and older. Here, we report findings from an infant adverse event survey in 1-5 month olds who received azithromycin as part of a large community-randomized trial in Niger. METHODS AND PRINCIPAL FINDINGS:Active surveillance of infants aged 1-5 months at the time of treatment was conducted in 30 randomly selected communities from within a large cluster randomized trial of biannual mass azithromycin distribution compared to placebo to assess the potential impact on child mortality. We compared the distribution of adverse events reported after treatment among azithromycin-treated versus placebo-treated infants. From January 2015 to February 2018, the caregivers of 1,712 infants were surveyed. Approximately one-third of caregivers reported at least one adverse event (azithromycin: 29.6%, placebo: 34.3%, risk ratio [RR] 0.86, 95% confidence interval [CI] 0.68 to 1.10, P = 0.23). The most commonly reported adverse events included diarrhea (azithromycin: 19.3%, placebo: 28.1%, RR 0.68, 95% CI 0.49 to 0.96, P = 0.03), vomiting (azithromycin: 15.9%, placebo: 21.0%, RR 0.76, 95% CI 0.56 to 1.02, P = 0.07), and skin rash (azithromycin: 12.3%, placebo: 13.6%, RR 0.90, 95% CI 0.59 to 1.37, P = 0.63). No cases of infantile hypertrophic pyloric stenosis were reported. CONCLUSIONS:Azithromycin given to infants aged 1-5 months appeared to be safe. Inclusion of younger infants in larger azithromycin-based child mortality or trachoma control programs could be considered if deemed effective. TRIAL REGISTRATION:ClinicalTrials.gov NCT02048007.